2023
DOI: 10.3389/fimmu.2022.1068186
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of cfDNA-related innate immune responses in postoperative bone loss after alveolar bone grafting

Abstract: The purpose of treating alveolar bone cleft is to restore a normal maxilla structure. Multiple factors have been identified that can affect the success of alveolar bone grafting. However, with consistent treatment modifications, the surgical outcomes have been improved, but alveolar bone loss still exists. Thus, a new aspect should be found to solve this problem. As alveolar bone belongs to the periodontal tissues, the mechanism of the alveolar bone loss after bone grafting in patients with alveolar bone cleft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In fact, a study conducted by Huang et al [ 4 ] showed the relationship between high levels of cfDNA and elevated alveolar bone destruction in patients affected by periodontitis. In another study conducted by Huang et al [ 66 ], it was found that cfDNA actively participates in bone resorption. The authors evaluated this activity by measuring the cfDNA level in GCF of patients during the post-operative 24 h in the sites where bone grafting was inserted.…”
Section: Cfdna and Periodontitismentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a study conducted by Huang et al [ 4 ] showed the relationship between high levels of cfDNA and elevated alveolar bone destruction in patients affected by periodontitis. In another study conducted by Huang et al [ 66 ], it was found that cfDNA actively participates in bone resorption. The authors evaluated this activity by measuring the cfDNA level in GCF of patients during the post-operative 24 h in the sites where bone grafting was inserted.…”
Section: Cfdna and Periodontitismentioning
confidence: 99%
“…The authors evaluated this activity by measuring the cfDNA level in GCF of patients during the post-operative 24 h in the sites where bone grafting was inserted. From the results of this evaluation, it was observed that the bone loss obtained after the alveolar bone grafting may be related to increased cfDNA levels in GCF [ 66 ].…”
Section: Cfdna and Periodontitismentioning
confidence: 99%
See 1 more Smart Citation